PENGARUH PENAMBAHAN MASAMIX KWS DENGAN DOSIS BERBEDA DALAM RANSUM TERHADAP PERFORMA AYAM PETELUR - Hidayat Z. P, Zaeni; Kurtini, Tintin; Fathul, Farida (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2017)
This research was conducted in Juli-Agustus 2016 at layer farm in Sumber Sari, Taman Sari Village of Gedong Tataan District, Pesawaran Regency and Laboratory of Nutrition and Food Livestock, Animal Husbandry Departmen, Faculty of Agriculture, University of Lampung. This research aims to study 1) the effect of using feed additive on feed for performances; 2) optimum doses of feed additive in feed layer. This research used Completely Randomized Design with 4 treatments added feed additive with a dose of (0; 0,15; 0,25; and 0,35%), 5 replications, there were 20 experiment unit and each unit consists of 1 chicken. Material used in this research was 20 chickens strain of isa brown the age 48 weeks. The conclude that addition of feed additive with a doses of 0; 0,15; 0,25; 0,35% on feed influence insignificantly (P>0.05) to the performances (feed consumption, feed convertion, egg weight, hen-day, and income over feed cost (IOFC)) layer and not found optimum doses. Keywords: Feed Additive, Doses, Layer , Performance